A preliminary phytolith analysis of terrace soils from Buffelskloof, Mpumalanga, South Africa. Issue 4 (2nd October 2022) - Hattingh, Tanya; Bamford, Marion K.; Schoeman, Maria H.
ABSTRACT: Even though numerous studies have explored the layout, location, and chronology of Bokoni settlements of the second millennium AD (Mpumalanga province, South Africa), relatively little is known about the type of food cultivated by its people. In pursuit of direct evidence for crops and to understand the environmental conditions that prevailed during the site's occupation we conducted a phytolith analysis of sediments collected from a terrace at Buffelskloof (BFK1). While we were able to determine that Zea mays (maize) was not cultivated in the sampled terrace, we were not able to determine if any African domesticates were grown on the terraced area. Iph and Ic indexes were used to determine that BFK1 received more rainfall during the site's occupation than at present and temperatures fluctuated. The Broadleaf index (D/P°) was used to determine the amount of tree cover and showed that BFK1 was situated in an open grassland during some periods of the site's occupation.